2020
DOI: 10.1186/s12906-020-02967-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tai chi and Qigong exercise on depression and anxiety of individuals with substance use disorders: a systematic review and meta-analysis

Abstract: Background: Previous studies have acknowledged Tai Chi and Qigong exercise could be potential effective treatments for reducing depression and anxiety in both healthy and clinical populations. However, there is a scarcity of systematic reviews summarizing the clinical evidence conducted among individuals with substance use disorders. This study tries to fill up this gap. Methods: A systematic search using Medline, EMbase, PsychINFO, Eric, SPORTDiscus, CINAHL, the Cochrane Central Register of Controlled Trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 62 publications
2
40
1
3
Order By: Relevance
“…However, compared with the general exercise, Wuqinxi has a better effect on mental health, and the difference is statistically significant (P < 0.05). A large number of studies confirmed that qigong was more beneficial to psychology than general exercise, which was also consistent with our research results [41][42][43]. Besides, the patients with chronic LBP in the WQXG or GEG had a significant improvement on the sleep quality of at 24 weeks compared with baseline, according to the changes in PSQI scores.…”
Section: Analysis Of the Research Resultssupporting
confidence: 90%
“…However, compared with the general exercise, Wuqinxi has a better effect on mental health, and the difference is statistically significant (P < 0.05). A large number of studies confirmed that qigong was more beneficial to psychology than general exercise, which was also consistent with our research results [41][42][43]. Besides, the patients with chronic LBP in the WQXG or GEG had a significant improvement on the sleep quality of at 24 weeks compared with baseline, according to the changes in PSQI scores.…”
Section: Analysis Of the Research Resultssupporting
confidence: 90%
“…According to a number of studies, different MBEs are reported to have positive impacts on some aspects that are severely influenced by SUD (25,26). Qi gong meditation contributes positively to addiction treatment outcomes, and meditative therapy may be more attractive for female drug abusers than for males (27).…”
Section: Positive Effects Of Mbe On Sudmentioning
confidence: 99%
“…Similarly, enhanced life quality of illicit drug users was found following 12 weeks of TC exercise ( 67 ). TC also had a beneficial effect on the depression and anxiety symptoms of drug dependents ( 68 ). Therefore, TC may be an effective intervention for the physical fitness and EFs of female MA dependents.…”
Section: Introductionmentioning
confidence: 99%